1995
DOI: 10.1002/hep.1840210333
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal high-intensity focused ultrasound for VX2 liver tumors in the rabbit

Abstract: High-Intensity Focused Ultrasound (HIFU) can produce radical tissue necrosis. We wanted to assess tumor destruction, proliferation, and tumorigenesis after HIFU, in an animal model of hepatic tumor. New Zealand rabbits bearing VX-2 solitary liver tumors were treated with extracorporeal HIFU under ultrasound (US) guidance and standardized conditions. Groups differed only for the administration of either one or two consecutive HIFU procedures. Tissue destruction was assessed by stereomicroscopy and planimetry, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…The energy deposition of focused US on the target tissue causes coagulative necrosis of tumours (Chapelon et al, 1992;Chen et al, 1993;Sibille et al, 1993;Prat et al, 1995;Rowland et al, 1997). In this study, pathological examination revealed that both breast cancer cells and normal tissues within the treated region presented a typical appearance of coagulative necrosis with severe nuclear damage.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The energy deposition of focused US on the target tissue causes coagulative necrosis of tumours (Chapelon et al, 1992;Chen et al, 1993;Sibille et al, 1993;Prat et al, 1995;Rowland et al, 1997). In this study, pathological examination revealed that both breast cancer cells and normal tissues within the treated region presented a typical appearance of coagulative necrosis with severe nuclear damage.…”
Section: Discussionmentioning
confidence: 64%
“…These advantages make it one of the most attractive potential therapies for the localised treatment of tumour. To our knowledge, most of the studies on HIFU have been dealing with animal experiments in which HIFU has induced target lesions at depth in tumour tissues and normal organs, including liver, kidney, prostate, bladder, and soft tissue (Chapelon et al, 1992;Chen et al, 1993;Sibille et al, 1993;Prat et al, 1995;Rowland et al, 1997).…”
mentioning
confidence: 99%
“…114 The use of local irradiation using 90 yttrium seed implants has also been reported. 115 Intratumoral ethanol injection, a therapy that has gained wide acceptance for unresectable hepatocellular cancer, 116 is less effective in ethanol metastatic lesions, which are denser and result in with less capacity for diffusion.…”
Section: Cryosurgery and Other Forms Of Local Hepatic Ablative Therapymentioning
confidence: 99%
“…HIFU techniques for solid tumors treatment have been reported as noninvasive and conformal with real-time monitoring [10,11] . In animal experiments and clinical studies, it has been proven that HIFU can selectively target and destroy primary or metastatic lesions through intake skin, thereby treating tumors in the liver [10,12,13] or other solid organs such as kidney [14][15][16] , bone [17] , prostate [18][19][20] , pancreas [21] , etc. Although HIFU treatment for recurrent and metastatic abdominal tumors was generally thought to be noninvasive and safe, we observed some common and even severe complications in our practice, and the aim of this study was to analyze the local and systemic complications of HIFU in patients with recurrent and metastatic abdominal tumors.…”
Section: Introductionmentioning
confidence: 99%